Electrochemical biosensor for the detection of a sequence of the TP53 gene using a methylene blue labelled DNA probe. (20th August 2021) - Otero, Fernando; Shortall, Kim; Salaj-Kosla, Urszula; Tofail, Syed A.M.; Magner, Edmond
Abstract: The development of an electrochemical biosensor utilising a hairpin DNA probe labelled with methylene blue for the detection of the TP 53 gene is described. Structural rearrangement of the hairpin probe into a linear double DNA strand induced different rates of electron transfer that enabled an increase in current upon hybridization. The increase in current observed upon hybridization was studied at different surface probe densities, hybridization times, concentration and length of target DNA sequences. The biosensor selectively detected a single nucleotide polymorphism in the TP53 gene affecting residue 175 of the p53 protein, with the response more pronounced at shorter hybridization times. Detection of target DNA sequences at nanomolar concentrations was achieved and the sensor possessed good operational and storage stability.